Revegetation of areas degraded by mining in the cerrado: the use of sewage sludge in soil rehabilitation - Garcia, Ana Raquel de Mesquita; Corrêa, Rodrigo Studart (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Among the activities that negatively impact areas of the Brazilian Cerrado biome, mining is one of the most significant for the country’s economy, representing around 8% of its Gross Domestic Product (GDP). However, mining causes serious environmental damage, requiring chemical, physical and biological rehabilitation of the exposed substrate to start ecosystem recolonization. Mine rehabilitation for revegetation requires adding large amounts of organic matter to exposed substrates. Studies on using domestic sewage sludge as an organic matter and nutrient source for plants have yielded significant results in ecological restoration protocols. This article presents a traditional narrative review of the literature related to the ecological, chemical, and physical processes in the application of sewage sludge for rehabilitating mining substrates in the Cerrado. It analyzed 95 articles, from 1985 to 2023, across 72 scientific journals. The results show that applying sewage sludge at rates bellow 100 t ha-1 (dry basis) raised soil pH and iron concentration, stabilized carbon, increased water availability, and decreased invasive plant recruitment. Additional techniques include sowing plants with functional characteristics similar to those of invasive species, increasing the functional diversity of species in plant communities, and identifying and manipulating ecological filters to stimulate the recruitment of native plant species. Soil-plant feedbacks determine crucial points for ecosystem balance and regulate available resources. Treatment with sewage sludge at rates bellow < 100 t ha-1 (dry basis) optimized the physical, chemical, and biological characteristics of exposed substrates, accelerating the colonization of plant communities and demonstrating the need for continuous monitoring of interactions between the edaphic environment and plants to establish biological diversity.